UPAYA MENINGKATKAN KINERJA GURU MELALUI SUPERVISI KEPALA MADRASAH DI MAN I PADANG TAHUN PELAJARAN 2021/2022 - MARLIZA MARLIZA (LP2MTBM MAKARIOZ, 2023)
The existence of supervisors in the world of education has an important role in fostering and selecting teachers. A similar reality also happened in MAN 1 Padang. Based on observations, summative test scores (end of semester), Formative test scores (daily tests) decreased on average. There are many possible factors that cause low student achievement, one of which is decreased teacher performance. The purpose of this research is that this research can improve the quality of learning in MAN, through the creation and use of methods in accordance with the direction of the existing curriculum. By improving teacher performance, it is expected to increase student achievement. With the supervision of the head of the madrasah can improve teacher performance in the learning process. The type of research used in this study is the school action research method (PTS). The research location was carried out at MAN 1 Padang. The research was conducted in August 2021. The subjects of the research on the actions of the head of the madrasah were 64 teachers of MAN 1 Kota Padang. The data collection technique from this school action research is through quantitative data obtained from observations and interviews. The data analysis technique used in this study is quantitative data analysis sourced from instrument acquisition. The results showed that with this study there was an increase in student achievement in the learning process. There is an increase where students are more active in the learning process. The increase in teacher performance in the learning process is from the first cycle 74.3%, increasing in the second cycle 80.04% in the Good category (B). Improving the quality of education in MAN 1 Padang City in 2021/2022.